Age-related hallmarks of psychopathology in Cornelia de Lange and Rubinstein-Taybi syndromes. (July 2022) - Giani, Ludovica; Michelini, Giovanni; Ajmone, Paola Francesca; Scaini, Simona; Selicorni, Angelo; Vizziello, Paola; Costantino, Antonella
Abstract: Background and aim: There is mounting evidence highlighting that Cornelia de Lange Syndrome (CdLS) and Rubinstein-Taybi Syndrome's (RSTS) behavioral phenotypes are not stable over individual developmental trajectories and that several psychiatric disorders might arise with age. Our study aims to examine the specific hallmarks of psychopathology and behavioral phenotypes in four different age ranges: infancy and toddlerhood, early childhood, middle childhood, and adolescence, in both genetic syndromes. Method: The sample included 44 patients with CdLS (48% boys, age = 6.67 ± 4.36) and 31 with RSTS (48% boys, age = 6.89 ± 4.58) recruited through follow-ups. Cognitive, behavioral, and autism assessments were carried out with Griffith's scales or the Leiter-R, the Child Behavior Checklist, and the Child Autism Rating Scales 2. Multiple ANOVA 2 × 4 were run to outline behavioral phenotypic age-related syndromic markers and ANCOVA to value the weight of IQ and ASD-related traits on the psychopathological outcome. Results: Findings showed that anxiety is a crucial phenotypic hallmark, independent of IQ but associated with autistic traits, that increases from infancy to adolescence in both CdLS and RSTS. Conclusion and implications: Being aware of the developmental challenges that growing children are called to face is essential for drawing up proper standards of assessment turning into target age-related interventions, ensuring these patients personalized healthcare and improvement in life quality.